Developing a Port Energy Management Plan: Issues, Challenges, and Prospects. Issue 1 (2016) - Boile, Maria; Theofanis, Sotirios; Sdoukopoulos, Eleftherios; Plytas, Nikiforos
Raising the environmental profile of European ports and promoting excellence in port environmental management and performance are key priorities for European ports policy. The need for well-connected port infrastructure, efficient and reliable port services, and transparent port funding is significant. Reducing energy consumption in ports has become a major concern for all port community stakeholders and ranks third in the top 10 environmental priorities of the European port sector for 2013. This concern has led 57% of European ports to develop energy efficiency programs and 20% of them to adopt measures for directly producing energy from renewable sources. This paper presents a structured approach for developing a port energy management plan (EMP) that highlights the main issues, challenges, and prospects that should be taken into account. The role of European ports in changing energy policy is discussed, and the value of a port EMP, either at the port authority level or at the terminal operator level, is highlighted. Pertinent issues for developing such a plan are described and analyzed. Insight gained from the implementation of the approach in six Mediterranean ports, within the context of the Greenberth project, is reported, and targeted recommendations and conclusions are provided about how this diverse experience can contribute to a robust port EMP.